Novel GBS-Based SNP Markers for Finger Millet and Their Use in Genetic Diversity Analyses - Brhane, Haftom; Haileselassie, Teklehaimanot; Tesfaye, Kassahun; Ortiz, Rodomiro; Hammenhag, Cecilia; Abreha, Kibrom B.; Geleta, Mulatu (Frontiers in Genetics, 2022)
Genomic tools are required for the characterization of crop gene pools and for their genomics-led breeding. In this study, a high-throughput sequencing based characterization of finger millet germplasm representing diverse agro-ecologies was considered as an effective method for determining its genetic diversity, and thereby suggesting potential candidates for breeding. Here, genotyping-by-sequencing (GBS) method was used to simultaneously identify novel single nucleotide polymorphism (SNP) markers and to genotype 288 finger millet accessions collected from Ethiopia (228 landraces and 14 cultivars) and Zimbabwe (46 landraces). The accessions were characterized at individual and group levels using 5226 bi-allelic SNPs, with minimum allele frequency (MAF) of above 0.05, distributed across 2500 scaffolds of the finger millet reference genome. The polymorphism information content (PIC) of the SNPs was 0.23 on average, and a quarter of them have PIC values over 0.32, which make them highly informative. By grouping the 288 accessions into seven populations based on geographic proximity and the potential for germplasm exchange, a narrow range of observed heterozygosity (Ho; 0.09-011) was observed, whereas expected heterozygosity (He) ranged over twofold, from 0.11 to 0.26. As revealed by analysis of molecular variance (AMOVA), highly significant genetic differentiation exists among groups of accessions classified based on the geographic region of origin, country of origin, days to flowering, panicle type, and Al-tolerance (P < 0.01). The high genetic differentiation between Ethiopian and Zimbabwean accessions was evident from the AMOVA, cluster, principal coordinate, and population structure analyses. Alleles unique to the different groups were also identified, which merit further investigation for their potential association with desirable traits. For finger millet landrace accessions from different geographic regions within Ethiopia, the level of genetic variation varied moderately, with accessions from the northeastern region having the lowest genetic diversity. In the neighbor-joining cluster analysis, most of the improved cultivars included in this study were closely clustered, probably because they were developed using genetically less diverse germplasm and/or selected for similar traits, such as grain yield. The recombination of alleles via crossbreeding genetically distinct accessions from different regions of the two countries can potentially lead to the development of superior cultivars.